ANALISIS DAN PROYEKSI INDIKATOR EKONOMI MAKRO PROVINSI MALUKU TAHUN 2018 - 2022 - Djufri Rays Pattilouw (Jurnal Cita Ekonomika, 2018)
This study aims to evaluate and forecast macroeconomic achievements for the next five years, covering four main macroeconomic indicators, namely economic growth, inflation, poverty and unemployment. The methodology used includes estimating the Autoregresive moving average (Arima) model, elasticity approach, central tendency, and landscape analysis. The results of the study concluded that: 1) Maluku's economy in the next five years is estimated to experience a slight increase with an average economic growth of 6.4 percent; 2) In line with the increase in economic activity inflation is also predicted to increase proportionally at an average of 3.1 percent for Ambon inflation, and 3.9 percent for Tual inflation; 3) Unemployment is predicted to decline with an average decline of 0.3 percent annually, while the poverty rate is also predicted to decline with an average decline of 0.6 percent per year. The implication of this finding is that optimistic expectations for Maluku's future economic outlook should be able to be responded to through more progressive, effective and efficient APBD policies, as well as increasing the synergy of valid and uniform data-based programs, both across sectors and across districts / cities.